1962
DOI: 10.1002/hlca.19620450210
|View full text |Cite
|
Sign up to set email alerts
|

16‐epi‐Gitoxigenin und 3‐O‐Acetyl‐17βH‐gitoxigenin

Abstract: Uzarigenin lasst sich durch Erhitzen rnit Na-Tosylat in Dimethylformamid relativ leicht in die 17BH-Verbindung uberfuhren l). Die analoge Isomerisierung beim Digitoxigenin ist von FRERE JACQUE bzschrieben worden2). Die Struktur dieser 17/?HButenolide ist in beiden F a e n sichergestellt worden. Vor kurzem haben REICHSTEIN und Mitarb. 3, auch Corotoxigenin, Coroglaucigenin und Gitoxigenin dem eingangs erwahnten Isomerisierungsverfahren unterworfen. Ein Beweis fur die 17pH-Konfiguration der dabei erhaltenen Reak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1965
1965
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…15-Oxodigitoxigenin (XCV) was shown to be biologically active whereas 15a-hydroxydigitoxigenin (XCVI) was inactive (35,36). One study (101) showed that 14a-artebufogenin (XCVII) was inactive where-as the 14P-isomer (XCVIII) was active. The corresponding butenolide analogs (XCIX and C) were both inactive.…”
Section: Scheme Xi-synthesis Of C-l7-trans-(e)-ab-unsaturated Estersmentioning
confidence: 99%
“…15-Oxodigitoxigenin (XCV) was shown to be biologically active whereas 15a-hydroxydigitoxigenin (XCVI) was inactive (35,36). One study (101) showed that 14a-artebufogenin (XCVII) was inactive where-as the 14P-isomer (XCVIII) was active. The corresponding butenolide analogs (XCIX and C) were both inactive.…”
Section: Scheme Xi-synthesis Of C-l7-trans-(e)-ab-unsaturated Estersmentioning
confidence: 99%
“…When compared to the other methods which use SPE procedures [14,17], this method has the advantage of giving better extraction yields [14] and being more rapid and feasible [17].…”
Section: Discussionmentioning
confidence: 99%
“…Fluorimetric detection after derivatisation has been also reported [15]. An automated HPLC determination of CAs in rat plasma using the peroxyoxalate chemiluminescence reaction has also been reported [16], as well as chemiluminescence determination of CAs in human blood plasma using 1,2-bis(3-chlorophenyl)ethylenediamine as a derivatisation reagent [17]. Recently, we developed an HPLC method with coulometric detection with a careful SPE procedure for the extraction of CAs from plasma, based on their complexation with diphenylborate [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6,7] The quantification of adrenaline in body fluids is an important challenge in biosensor development. Until now, high-performance liquid chromatography (HPLC) with electrochemical [8][9][10] or optical [11] detectors has been frequently used to detect catecholamines. Although catecholamines can be selectively detected from ascorbic acid and uric acid by HPLC, this technique requires a pre-treatment process, and the detection measurements can be time consuming.…”
Section: Introductionmentioning
confidence: 99%